National security analytical activities organizational models classification - Sokolov, Vadim (Aspekty publichnoho upravlinni͡a, 2020)
The purpose of the article is to elaborate a national security analytical activities organizational models classification.The relevance of the research stems from the fact that Ukraine’s integration to the Euro-Atlantic and European security systems in the context of dynamic security environment sets for the national security state management system a task of elaborating and urgent implementing into the state managerial practice a fundamentally new national security analytical activities organizational model.Comparative-historical method and method of synthesis were used to meet the tasks of the research. The author suggests understanding under the concept «national security analytical activities organizational model» a formalized reflection of a process of establishing national security system analytical activities organizational structures, developing rational organizational relations between the subjects of the above-mentioned activities. The results of the USA, Germany, Russian Federation and China national security analytical activities conceptual bases comparative-historical analysis, and also the results of the analytical activities institutional matrices comparative study, allow to classify the analytical activities organizational models according to the criterion of analytical structures activities organization form into bureaucratic-nomenclatural and cooperative organizational models. The article characterizes bureaucratic-nomenclatural and cooperative organizational models within the national security system by the following components: analytical structure mission, goals, objectives, the way of structural organization, structural organization elements, the specific of cooperation between an analytical structure and the government, typical conditions for analytical structure activities. Conclusion. It is identified that the USA and Germany tend to have a cooperative organizational model of a national security system analytical activities, the Russian Federation, China, and Ukraine – bureaucratic-nomenclatural organizational model. In order to improve the national security state management system of Ukraine in terms of Euro-Atlantic and European integration objectives it is suggested to identify a cooperative model as a perspective organizational model within the national security system analytical activities.